The change of tendencies in the German-Russian relations : The case of Ukrainian crisis - Oliichuk, Vitalii; Votoupalová, Markéta; Lobastova, Svetlana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
Armed conflict in Eastern Ukraine created a security crisis in the EU and escalated the German-Russia relations that were in a cool-off period for a long time. The analysis of German actions is an essential aspect in understanding of the Ukrainian crisis, as Germany (being a leader in its settlement) strongly influences the course of events not only in Ukraine but also in Europe.
Vedoucí práce: Markéta Votoupalová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses